El sistema de ahorro de la Cooperativa Codesarrollo, bajo la óptica de la economía popular y solidaria. - Pérez Chávez, Jonnathan Alejandro (2014)
This investigation overall aims to develop proposals to increase savings indicators Cooperative Codesarrollo level and the institutions with which it works, as well as optimizing the performance of programs and savings plans, evaluate the perception of the customers regarding savings and implement system improvements and evaluate their performance within the Popular Finance. Insufficient savings culture, consumerism trend, the lack of vision of solidarity, among other factors, are responsible for the poor people, not realizing their business potential and community is for this reason that the proposal is tied to the popular finance application that is a powerful element to overcome poverty. Its starting point is the savings, which is achieved by producing more than they consume and stimulating in every person's self-control and programming.